Rosai Dorfman Disease of Kidney: Report of a Rare Case - Kushwaha, Pritika; Khuraijam, Bembem; Khurana, Nita; Vindal, Anubhav (Annals of Pathology and Laboratory Medicine, 2023)
Rosai Dorfman Disease (RDD) is a type of histiocytoses usually affecting the lymph nodes. Extranodal involvement by RDD can occur, although, infrequently. However, extranodal RDD without a prior history of the nodal variant of the disease is rare. Present case report highlights this rare occurrence. A 75 years old female presented with left renal mass with no significant previous medical or surgical history. PET-CT scan revealed two solid lobulated mass in the left kidney, suggesting Renal Cell Carcinoma. Radical nephrectomy was performed, which on histopathological examination showed features of RDD and was confirmed subsequently by immunohistochemical and special stains.